If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + -1x = 0 Solving -12 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -1x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = 0 + 12 -1x = 0 + 12 Combine like terms: 0 + 12 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12
| (4x)=(5x-3) | | 3x^3-5x^2+48x-80=0 | | 2x+5y-6=6 | | j=12 | | 3x+y(0)=-3 | | -40m+84= | | 3-6*3+2=X | | 6j-j-2j+j=20 | | 2(5+y)=-18 | | 6w^2-54= | | 20k-14k-2=10 | | -12x+6y=8 | | 4y+2=y+2 | | 5y-4=y+2 | | -8(x+7)+60=9-9x | | 4b-14b-17=65 | | 5y-4=4y-2 | | 7r=(-5r)+144 | | 2n+3=15-n | | 10(0)-5y=20 | | 10x-5(0)=20 | | 35+(25+r)=r | | (y^2)-2y=(x^3)+2(x^2)+2 | | 15g+3g-17g+g+1=15 | | 3/9*23+(7*8)= | | 20x-4y=-12 | | 3x+21y=21 | | 3(x+7)-3=53-2x | | 4(3x)=512 | | -8q+-9+-q+8=-10 | | -6+4x=-9 | | t(3-4t)=o |